Managing the effects of presenteeism on productivity of a company in the foodtransformation sector - Cunha, Márcia (2016)
Presenteeism consists in going to work without conditions to produce, which can have a much higher impact than absenteeism on the productivity of an organisation. Presenteeism translates in both physical (low back pain, headache, arthritis) as psychological perturbations (anxiety, depression, stress, attention deficit). It is a difficult to quantify reality as is its translation into direct and indirect costs within the organisation. Goal: Analyse the effects of presenteeism on the productivity of a company in foodprocession sector. Method: Study of exploratory nature, descriptive and transversal, using a case study. The Stanford Presenteeism Scale SPS-6 (validated by Ferreira et al, 2010) and a semistructured interview to the management were used. Results: Most of the workers referred having already gone to work feeling ill at least two days in the last year, mentioning that their health condition affected their performance, feeling desperate and lacking pleasure from the tasks. The incidence of presenteeism varied according to the function performed in the company being that there was a higher incidence in the more demanding functions. Management mentioned that presenteeism has a direct impact on productivity without, however, being able to quantify the true costs. Conclusions: Presenteeism is a reality in the organisational scenarios, exceling in the educational and health sectors. We underline the importance of making organisations aware of the psychosocial risks and the importance of having healthy leaderships, work stress control and the presence of clinical psychologists and professional coaches.